Cooperative Midcourse Guidance Law with Communication Delay. (11th September 2021) - Wu, Zihao; Ren, Quanbin; Luo, Zhiqing; Fang, Yangwang; Fu, Wenxing
Abstract : The initial conditions of the cooperative terminal guidance law, which are the terminal conditions of the cooperative midcourse guidance, have a greater impact on its cooperation and guidance precision, so it is worthy of investigating the cooperative midcourse guidance. In addition, the problem of communication delay between the network nodes is inevitable and has a greater impact on the cooperative guidance law. To solve the above problems, a novel distributed cooperative midcourse guidance (DCMG) law with communication delay is proposed by combining the cooperative term with a distributed consensus protocol including communication delay under the directed communication topology. Firstly, a DCMG law with communication delay is designed by combining the trajectory shaping guidance with the distributed protocol including communication delay under the directed communication topology; secondly, the consensus of the proposed DCMG law with communication delay under the directed graph is proved; finally, the effectiveness and superiority of the proposed DCMG law are verified by numerical simulations.